The Effect of Efficiency, Market Ratio, Liquidity and Leverage on Financial Performance: Evidence from Jakarta Islamic Index 70 (JII70) - Happiness Zana; Suryo Budi Santoso; Dwi Winarni; Bima Cinintya Pratama; Ira Hapsari (Economics and Business Journal (ECBIS), 2026)
Companies listed in the Jakarta Islamic Index 70 (JII70) provide a unique research context because they operate within an Islamic capital market framework that applies sharia screening criteria and financial requirements. Despite being guided by the same sharia principles and regulatory environment, JII70 companies still show variations in financial performance. Although previous research has examined the factors that affect financial performance, empirical evidence regarding the influence of efficiency, market ratios, liquidity, and leverage still shows inconsistent results, particularly in companies that comply with sharia principles. Therefore, this study aims to analyze the influence of efficiency, market ratio, liquidity, and leverage on the financial performance of companies listed on JII70 by using Return on Assets (ROA) as a performance indicator. This study uses a quantitative approach by utilizing secondary data obtained from the annual reports of 57 non-financial companies during the period 2021–2025, resulting in 285 company-year observations. Panel data regression analysis was performed using the Fixed Effects model with Driscoll–Kraay error standard to overcome the problems of heteroscedasticity and autocorrelation. The results show that efficiency measured by Total Asset Turnover (TATO) and market ratio measured by Price-to-Book Value (PBV) have a positive and significant effect on financial performance. Meanwhile, liquidity measured by Current Ratio (CR) and leverage measured by Debt-to-Asset Ratio (DAR) have a positive but not statistically significant effect on financial performance. The findings of this study support the Signaling Theory by showing that efficiency and market ratio provide stronger signals regarding company quality and financial performance in the context of the Islamic capital market in Indonesia. These findings provide practical implications for managers in improving company performance as well as for investors in making more informed investment decisions